Analysis of the diagnosis of the mathematical competence Problem Solving in three rural educational institutions in Colombia - Orozco-Carvajal, Carlos A. (2023)
The purpose of this article is to analyze the results of a diagnostic test in order to determine the aspects, weaknesses and/or difficulties presented by tenth grade students of three educational institutions located in the rural area of the municipality of Garzón (Huila), institutions that have the modality or technical high school graduates in agriculture and livestock. The support of this research is the Holistic Understanding of Science of Hurtado (2010), it is developed through the Holopraxis method and thus reach an apprehensive level of the study event, which is the mathematical competence Problem Solving. To analyze the results of this research, thirteen mathematical problems with open questions are designed in order to determine the use of the Pólya method by the students to solve them, whose structure is organized in the synergies Comprehension, Planning, Application and Approval, and are crossed with the mathematical thoughts such as the Numerical-variational, Geometric-metric and Random. Among the aspects found are the medium performances obtained by the students according to a scale of scores (Baremo) or the low performances according to a parallelism of the Colombian numerical valuation scale. Likewise, the importance of generating curiosity, creativity, motivation and willingness in students is highlighted, in order to comprehensively develop the mathematical competence Problem Solving.